Processes of consumer socialization: study of single-father households. (10th June 2021) - Harrison, Robert; Moisio, Risto; Gentry, James; Commuri, Suraj
Abstract : Purpose: Despite years of research into consumer socialization, little research examines men's roles in consumer socialization processes. The purpose of this paper is to attend to this gap and to investigate consumer socialization processes in single-father households. Design/methodology/approach: To study consumer socialization processes, this paper develops its insights using grounded theory, deploying qualitative data to develop theory. The data include long interviews with both fathers and their children used to understand the processes of consumer socialization. Findings: This paper finds six socialization processes: entrustment, entrainment, education, emprise, estrangement and elevation. These processes emerge based on different types of household resource gaps or aspects of men's gender identity. Research limitations/implications: The main implications are to study the roles played by cultural context and family type in socialization processes. Studies could examine whether the processes uncovered here occur in other family settings, as well as whether they vary based on children's age and gender. Practical implications: Household brands, products and services could target resource-scarce households using appeals that portray offerings as a means to develop children's responsibilities, independence and involvement in household management. Marketers could also use advertising appeals that depict playful product usage and learning situations or more broadly position brands as identity brands making them more appealing to men who are striving to be better fathers. Originality/value: This paper uniquely identifies a number of previously uncovered consumer socialization processes, as well as factors that influence them.